2022
DOI: 10.57092/ijetz.v1i2.37
|View full text |Cite
|
Sign up to set email alerts
|

Development of Interactive Learning Media as an Alternative to Improve Students' Conceptual Understanding and Motivation on the Temperature and Heat Topics

Abstract: This study aims to develop and determine the feasibility of interactive learning media on the topic of temperature and heat. The type of research is Research and Development (R&D) with the ADDIE model. In this model, the stages include Analyze, Design, Develop, Implement, and Evaluate. However, this research is only up to the development stage. The subjects of this study were 20 students from one of the XI MIPA classes at Panjura High School. The interactive media was developed in the form of an android-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…From the results of an interview with the person concerned, to whom we asked several questions, it was found that as a result of playing on the internet, there are children who have positive and negative consequences. From the interviews that have been conducted, there are 16 pieces of information that have positive consequences, namely playing on the internet and social media, namely for parents because children do not play outside the house or do not play too far from home, with that parents feel their children are better off because that way the child not joining bad associations from the outside, parents also feel the positive impact of playing because children can still be controlled, with time they can still be divided up for studying, eating and other activities (Bahrudin & Yogihati, 2022;Yusuf et al, 2022;Zb et al, 2022). We have also received information from negative impacts from parents and their children playing on the internet that children forget and are lazy to study, eat and do other activities.…”
Section: Resultsmentioning
confidence: 99%
“…From the results of an interview with the person concerned, to whom we asked several questions, it was found that as a result of playing on the internet, there are children who have positive and negative consequences. From the interviews that have been conducted, there are 16 pieces of information that have positive consequences, namely playing on the internet and social media, namely for parents because children do not play outside the house or do not play too far from home, with that parents feel their children are better off because that way the child not joining bad associations from the outside, parents also feel the positive impact of playing because children can still be controlled, with time they can still be divided up for studying, eating and other activities (Bahrudin & Yogihati, 2022;Yusuf et al, 2022;Zb et al, 2022). We have also received information from negative impacts from parents and their children playing on the internet that children forget and are lazy to study, eat and do other activities.…”
Section: Resultsmentioning
confidence: 99%
“…Education is learning understanding, insight and skills carried out by individuals and groups of people through teaching, guidance, and training that has become a hereditary habit from generation to generation. Education has an important position in improving the quality of creative, productive and innovative human resources in determining the progress of a nation and state (Bahrudin & Yogihati, 2022;Masalesi, 2022;Zakwandi et al, 2022). To become a human being with noble character and to become a human being who believes and fears God Almighty, it is necessary to have a good education.…”
Section: Introductionmentioning
confidence: 99%